Changes on the Physical-Chemical Properties of Kue delapan Jam on Various Steaming Time - Sri Agustini (Chemical Engineering Diponegoro University, 2014)
This research intended to study browning reaction between glucose, fructose, and lipids with amino acids in real system during making Kue Delapan Jam. Research applied completely randomized design with steaming time as treatment ( 2, 4, 6, and 8 hours) with 3 replication. The development of color and browning index were ivestigated by using lightness, redness, yellowness, and total color difference (TCD) during reaction, and the absorbance of methanol extracts was measured at 420 nm in 40.0 mm silica. The development of texture was monitored by using Bookfield texture analyzer. Test results showed that steaming time influenced the color, browning index, texture, protein, and fat content of the cake significantly. Steaming time has no effect on water content. There were positive correlation between steaming time with TDC, redness, texture, and browning index during course. While for lightness, yellowness, pH, protein, and fat content indicated negative correlation. Changes on texture, TDC, browning index, protein, and fat content followed linear model.